Caries progression in non-cavitated fissures after infiltrant application: a 3-year follow-up of a randomized controlled clinical trial - ANAUATE-NETTO, Camillo; BORELLI NETO, Laurindo; AMORE, Ricardo; DI HIPÓLITO, Vinicius; D’ALPINO, Paulo Henrique Perlatti (Journal of Applied Oral Science, 2017)
Objectives To evaluate the efficacy of a conservative treatment to prevent the progression of caries using an infiltrant on non-cavitated pit and fissures. Material and Methods This controlled clinical trial selected 23 volunteers with clinically and radiographically non-cavitated occlusal caries among patients presenting a “rather low” to “very high” caries risk. Eighty-six teeth were randomly divided into two experimental groups: teeth receiving a commercial pit-and-fissure sealant (Alpha Seal-DFL) and contralateral teeth receiving Icon infiltrant (DMG). Caries progression was monitored by clinical (laser fluorescence caries detection) and radiographic examination at 12-month intervals over a period of 3 years of monitored caries progression. Probing the sealing materials to detect areas of retention was also used to evaluate marginal integrity. Results Statistical analysis showed no difference in caries progression using laser fluorescence caries detection when both materials were compared, regardless of the evaluation times (p>;0.05). No significance was observed when the marginal sealant integrity of both materials was compared, regardless of the evaluation time (p